2007
DOI: 10.1121/1.2409488
|View full text |Cite
|
Sign up to set email alerts
|

Coherent structures of the near field flow in a self-oscillating physical model of the vocal folds

Abstract: Current theories of voice production depend critically upon knowledge of the near field flow which emanates from the glottis. While most modern theories predict complex, three-dimensional structures in the near field flow, few investigations have attempted to quantify such structures. Using methods of flow visualization and digital particle image velocimetry, this study measured the near field flow structures immediately downstream of a self-oscillating, physical model of the vocal folds, with a vocal tract at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
95
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(104 citation statements)
references
References 64 publications
7
95
2
Order By: Relevance
“…In Fig. 4(d), a wavy pattern starts to develop in the downstream region (y > 4.0 cm).This wavelike pattern is termed as a "flapping jet" and is generated by an anti-symmetric array of countrotating vortices (Gordeyev and Thomas, 2000;Thomas and Brehob, 1986;Neubauer et al, 2007). The corresponding velocity vector plot [ Fig.…”
Section: B Glottal Jet Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Fig. 4(d), a wavy pattern starts to develop in the downstream region (y > 4.0 cm).This wavelike pattern is termed as a "flapping jet" and is generated by an anti-symmetric array of countrotating vortices (Gordeyev and Thomas, 2000;Thomas and Brehob, 1986;Neubauer et al, 2007). The corresponding velocity vector plot [ Fig.…”
Section: B Glottal Jet Evolutionmentioning
confidence: 99%
“…Intraglottal vorticity-velocity interaction, glottal jet structure, and its transition to turbulence are all demonstrated to be highly three-dimensional (3D) (McGowan, 1988;Neubauer et al, 2007;Triep et al, 2005;Triep and Br€ ucker, 2010;Zheng et al, 2011b). The 3D effects are clearly observed in the supraglottal region in both the experimental Triep and Br€ ucker, 2010;Khosla et al, 2007;Khosla et al, 2008) and numerical studies (Zheng et al, 2010b;Mattheus and Br€ ucker, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…A number of recent studies have shown that the largescale asymmetric glottal jet deflection (AGJD) in the mediallateral direction does occur during phonation both inside the glottis Plesniak, 2006a,b, 2010) as well as in the supraglottal region (Neubauer et al, 2007;Dreschsel and Thomson, 2008;Zheng et al, 2009). Furthermore, in many studies, the glottal jet has been found to exhibit stochastic cycle-to-cycle variations in its trajectory Plesniak, 2006a,b, 2010;Neubauer et al, 2007;Dreschsel and Thomson, 2008;Zheng et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This implies that the subglottal flow may be laminar. However, Neubauer et al [36] showed that near the glottal region, transition from laminar to turbulent flow occurs and that the supraglottal flow field, dominated by separated jet flow and recirculation, is rather turbulent. Numerical computation of such transitory, highly unsteady airflow with massive separation is problematic.…”
Section: Previous Work In the Fieldmentioning
confidence: 99%